THE TALE OF PASSING DOGS IN THE SMALL FAMILY FARM - Galindo, Dolores Cristina Gomes; Bianchini, Maria Leticia de Oliveira [UNESP]; Rodrigues, Renata Vilela; Zanata, Fernanda (FapUNIFESP (SciELO), 2024)
This article reflects on the uniqueness of the relationships between rural women and the dogs that constitute an interspecific relationship with them. It aims to tell about practices that emerged throughout research when we began to seriously consider the animal agency based on the daily life of a farmer researcher aligned with family agroecology. We focus on mixed breed dogs that come and go freely between the fences that delimit rural properties. In dialogue with Donna Haraway, Anna Tsing and Vinciane Despret, we present clues for multispecies research that operates through stories. Multispecies research invites us to reflect on anti-capitalist practices that germinate in agroecology, to focus on the work of women farmers and dogs in their power of self-government and to create forms of multispecific cooperation with significant alterities in the modern-colonizing project.
EL CUENTO DE LOS PERROS QUE PASAN POR LA GRANJA
O CAUSO DOS CÃES DE PASSAGEM NA ROÇA
Keywords: Agroecologia; Agroecology; Agroecología; Companion Dogs; Countryside; Cães de Companhia; Investigación Multiespecies; Multispecies Research; Perros de Compañía; Pesquisa Multiespécie; Psicologia Social; Psicología Social; Rural; Social Psychology